Trial and routine : on the problematic relation between routine care and "private actors" within West-African health services (Burkina Faso) - (:unkn) unknown (My University, 2013)
"Starting with the description of a clinical trial dealing with Prevention of Mother-to-Child Transmis- sion of HIV in Burkina Faso, this paper aims to discuss a recurrent aspect within the West-African public health services: the confusion of research and care and its implications. Analysis of the inclusion of this clinical trial is within the context of everyday care shows how rationales of research and daily care merge and transform the way care is organized and how they affect the aspect of trust and confidence which is at the heart of care interactions. This case is discussed with other activities like vertical programs structuring health care practices. This discus- sion argues for a shift in our understanding of health care services in Africa that included paying attention to the tensions and contradictions they contain. Acknowledging the multiple actors and logics present in the health care sector, this paper raises the issue of the possibility of a coherent and fair national public health policy."
Keywords: African Research